Body Mass Index of Elementary School Teachers Education 5th Semester STKIP Muhammadiyah Bangka Belitung - Wahyudhi Ramdhani; Deden Manggala Saputra; Wahyu Pratama; Indra Indra; M. Jordan (Journal Physical Education, Health and Recreation, 2020)
This study aims to determine the body mass index of elementary school teacher education 5th-semester students of STKIP Muhamadiyah Bangka Belitung, which was conducted in the STKIP MBB sports lab. The method used in this research is descriptive statistics. The population in this study were all of the 5th-semester PGSD students totaling 126 people and taking a sample used in total sampling. The instrument used was a body mass index test with the formula BMI = BB (Kg) / TB (m) 2. data analysis calculation techniques in research using quantitative approaches. The results of this study concluded that the average body mass index of PGSD 5th semester students STKIP MBB was 21.45 kg / m2, the minimum value was 14.6 kg / m2, and the maximum was 38.5 kg / m2. Based on the assessment of the body mass index, it can be concluded that the average semester 5 PGSD student STKIP MBB has a healthy body mass index.